Análise espaço-temporal de roubos e furtos de bicicletas na cidade do Rio de Janeiro - Ana Paula Vasconcelos Goncalves; Cassio Freitas Pereira de Almeida; Julia Celia Mercedes Strauch; Klarissa Almeida Silva Platero (Revista Transporte y Territorio)
In 2015, the government of the State of Rio de Janeiro instituted the system of prevention of bicycle theft and robberies and illegal bicycle trade and began to systematically publicize the occurrences of crimes against the bicycle. The prevention of bicycle thefts and robberies encourages the use of this mode by the population. In this way, this paper makes a spatial temporal analysis of the bicycle thefts and robberies in the neighborhoods of the city of Rio de Janeiro, between June 2015 and June 2017, in order to know the schedule, neighborhoods and places where this type of event occurs in the city. Among the results obtained, it observed that thefts occur less during the night and are more frequent in neighborhoods near the beach. Robberies occur more in the afternoon, are more concentrated in some neighborhoods and tend to follow the train line and the BRT route. Knowledge and understanding of the distribution of bicycle robbery and robbery events in the city of Rio de Janeiro are important for police planning and assistance to cyclists.